Reconstructing Epistemic Authority: A Post-Human Pedagogical Framework for Artificial Intelligence in Islamic Education - Suyono; Indi Aunullah; Moh. Nafi Alisha; Miftachul Huda; Halimatus Sa’diyah (Al-Qalam Institute, 2026)
The rapid entry of generative artificial intelligence into Islamic education raises a question that is epistemological before it is technical. As students increasingly turn to algorithmic systems to interpret texts and compose arguments, the authority over knowledge that has traditionally passed through morally formed scholars begins to shift toward systems that possess neither intention nor moral standing. This study reconstructs the epistemological relationship between artificial intelligence and the classical Islamic system of knowledge, and specifies a post-human pedagogical framework that integrates the human, the technological, and the theological without collapsing the hierarchy among them. Employing library research and conceptual analysis, the study draws its corpus through a PRISMA-guided search of Scopus and examines it through qualitative content analysis, reading the wider literature against the foundational work of al-Attas. The analysis reconstructs AI as an epistemic mediator rather than a neutral instrument, traces the structural tension between computational and revelatory logics, and shows how this tension is expressed differently across pesantren, madrasah, and Islamic higher education. The resulting framework subordinate’s algorithmic mediation to a descending hierarchy anchored in wahy (divine revelation), granting AI genuine epistemic participation while denying it epistemic authority, and culminating in the formation of adab (moral and intellectual virtue). The study contributes a constructive framework where existing scholarship has largely offered diagnosis, and extends transformative learning theory toward a post-human account. As a conceptual proposition, the framework awaits empirical testing in classrooms.